Innovative Geo-Information Tools for Governance - Reckien, Diana; Georgiadou, Yola (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In current times, highly complex and urgent policy problems—e.g., climate change, rapid urbanization, equitable access to key services, land rights, and massive human resettlement—challenge citizens, NGOs, private corporations, and governments at all levels. These policy problems, often called ‘wicked’, involve multiple causal factors, anticipated and unanticipated effects, as well as high levels of disagreement among stakeholders about the nature of the problem and the appropriateness of solutions. Given the wickedness of such policy problems, interdisciplinary and longitudinal research is required, integrating and harnessing the diverse skills and knowledge of urban planners, anthropologists, geographers, geo-information scientists, economists, and others. This Special Issue promotes innovative concepts, methods, and tools, as well as the role of geo-information, to help (1) analyze alternative policy solutions, (2) facilitate stakeholder dialogue, and (3) explore possibilities for tackling wicked problems related to climate change, rapid urbanization, equitable access to key services (such as water and health), land rights, and human resettlements in high-, middle-, and low-income countries in the North and South. Such integrative approaches can deepen our understanding of how different levels of government and governance reach consensus, despite diverging beliefs and preferences. Due to the particularly complex spatiotemporal characteristics of wicked policy problems, innovative concepts, alternative methods, and new geo-information tools play a significant role.